Nucleophilic ring-opening of benzoxazinones by dbu: some observations - Baravkar, Sachin B.; Roy, Arup; Gawade, Rupesh L.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Synthetic Communications, 2014)
This communication demonstrates the formation of an unusual nucleophilic ring opening of benzoxazinones by 1,8-diazabicycloundec-7-ene (DBU). This observation contradicts the intrinsic feature of a hindered nonnucleophilic base like DBU. Confirmation of the product was achieved via single-crystal X-ray diffraction studies.
Keywords: Benzoxazinones; caprolactam; DBU; HATU

Synthetic turn mimetics and hairpin nucleators: quo vadimus? - Nair, Roshna V.; Baravkar, Sachin B.; Ingole, Tukaram S.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
Structural mimicry of peptides has witnessed perceptible progress in the last three decades. Reverse turn and beta-hairpin units are the smallest secondary structural motifs that are some of the most scrutinized functional cores of peptides and proteins. The practice of mimicking, without altering the function of the bioactive core, ranges from conformational locking of the basic skeleton to total replacement of structural architecture using synthetic analogues. Development of heterogeneous backbones - using unnatural residues in place of natural ones - has broadened further opportunities for efficient structural rigidification. This feature article endeavours to trail the path of progress achieved hitherto and envisage the possibilities that lie ahead in the development of synthetic turn mimetics and hairpin nucleators.

Structural insights into the hydrogen-bonding and folding pattern in ant-ant-pro-gly tetrapeptides - Baravkar, Sachin B.; Kotmale, Amol S.; Mobin, Samir R.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2017)
In this paper, we provide structural insights into the hydrogen-bonding and folding pattern in Ant-Ant-Pro-Gly tetrapeptides (Ant: anthranilic acid; Pro: proline; and Gly: glycine). Comparison of the C-terminal esters and their amide analogs revealed strikingly different H-bonding networks. Whereas the ester analogs displayed an open structure without terminal H-bonding interactions, the amide analogs showed a completely folded structure. Structural details were revealed by using a combination of X-ray crystal structure studies and NOE-based molecular dynamics (MD) simulation studies.

Design and synthesis of 2-amino-thiophene-tethered ureidopenicillin analogs with potentantibacterial and antitubercular activity - Wagh, Mahendra A.; Baravkar, Sachin B.; Jedhe, Ganesh S.; Borkute, Rachna; Choudhari, Amit S.; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Ureidopenicillins are a class of penicillins which are antibiotics active against gram-negative bacteria. Herein, we report the synthesis of 2-aminothiophene-tethered ureidopenicillin analogues and their in vitro antibacterial and antitubercular activity. Intriguingly, unlike the reported ureidopenicillins which are active against gram-negative bacteria, the synthesised 2-aminothiophene-tethered ureidopenicillins were significantly active against Gram-positive bacterial strains and showed moderate inhibition towards gram-negative bacterial strains. Among all the analogs, compound 1b containing 2-aminothiophene moiety with minimum inhibitory concentration (MIC): 0.29, 0.32, > 10, > 10 mg/ml for Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, respectively, showed better anti-bacterial profile as compared to cephalexin and equipotent to ampicillin and amoxicillin on gram-positive bacterial strains. All the derivatives were also screened for anti-TB activity against mycobacterium tuberculosis H37Ra. Among the series, cycloocta-thiophene-tethered cephalexin analog 3c displayed excellent antitubercular activity with MIC values 0.78 mg/ml. Low cytotoxicity and high selectivity index indicate the efficacy of 3c against mycobacterial infections. The results from present study offer a novel approach to modify the existing drug class of ureidopenicillins to yield antimicrobials with promising utility.

Synthesis and anticancer activity of conformationally constrained Smac mimetics containing pseudo beta turns - Baravkar, Sachin B.; Wagh, Mahendra A.; Paul, Debasish; Santra, Manas; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2018)
Herein, we report synthesis and in vitro anticancer activity of conformationally constrained Smac mimetics containing reverse turn inducing motifs "Ant-Pro" and "sAnt-Pro". The synthesis of Smac analogs with diverse hydrophobic groups at the C-terminus was carried out using solution phase peptide synthesis. The synthesis of Ant-Pro containing analogs 3a-j was carried out by ring opening of benzoxazinones 7a-c, whereas, their sulfonamide counterparts 4a-h were synthesized by using routine acid-amine coupling reaction. In vitro anticancer studies against breast cancer cell line MDA-MB-231 revealed that some of the new analogs had better anticancer activity than the standard AVPI Smac tetrapeptide. (C) 2018 Published by Elsevier Ltd.

Design and synthesis of 2-amino-thiophene-proline-conjugates and their anti-tubercular activity against mycobacterium tuberculosis H37Ra - Baravkar, Sachin B.; Wagh, Mahendra A.; Nawale, Laxman U.; Choudhari, Amit S.; Bhansali, Sujit; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
The emergence of extensively drug resistant tuberculosis (XDRTB) and multi-drug resistant tuberculosis (MDR-TB) has necessitated the development of new drugs with short chemotherapy treatment regime and cost effectiveness. To overcome these challenges, we are reporting the synthesis of a series of 2-amino-thiophene-proline-conjugates which show potent invino and ex-vivo anti-tubercular (anti-TB) activity against mycobacterium tuberculosis (rntb) H37Ra. The synthesis of these 2-amino-thiophene-proline-conjugates was carried out via solution phase peptide coupling reactions using methyl-2aminothiophene-3-carboxylate 8 as an intermediate obtained by modified gewald reaction. Intermediate 8 was coupled with different amino acids to obtain dipeptides 3, 4, 5, 6a and 7. Priliminary anti-TB assay data encoureaged us to synthesize modified proline derivatives 6b-6k via formation of a benzoxazinone intermediate 16. Most of these conjugates are active against mtb H37Ra in both active (A) and dormant (D) strains. They are also active against drug resistant mtb H37Ra strains. A trifluoroethyl ester analog, 6i was the most potent among the series [MIC 1 mu g/mL] along with 6f and 6g [MIC 2-6 mu g/mL]. Cytotoxicity studies suggested that, these compounds are less cytotoxic to human cell lines HeLa, MCF-7, HUVEC and hence possess high selectivity index (SI). Docking studies revealed that the binding mode of most active compounds 6i, 6g and 6f is in accordance with their bioactivity studies having docking score 8.969, 8.446 and 7.865, respectively. More- over, in sllico ADME properties suggest that all the compounds possess drug like properties.
Keywords: 2-aminothiophene; Anti-tubercular; docking studies; Inh A gene; selectivity index